Decentralized EV charging and discharging scheduling algorithm based on Type-II fuzzy-logic controllers - Triviño-Cabrera, Alicia; López-Bueno, Alejandro; Yuste, Antonio J.; Cuevas, Juan C. (Elsevier, 2024)
Electric vehicles suppose a new paradigm in mobility and a challenge for today electric grids because its number increases day by day. Therefore, it is of paramount importance to keep the electric grid stable to allow an efficient charging of electric vehicles, besides keeping the traditional energy services for every other electric devices in industry, cities and homes. To achieve that, the process of charging and discharging of electric vehicles should be taken under consideration to allow an efficient use of the available energy in the grid and batteries. In the present work, we propose a type-II fuzzy cascade controller that will be run in every electric vehicle following a decentralized approach when it is plugged. In the first level of the controller the need and urgency of charging/discharging are evaluated based on grid voltage that the EV charging station measures. The electricity prices are also considered in this first phase. In the second level, the amount of charging/discharging energy is finally decided based on the battery state and the time remaining for departure specified by the user. The implemented type-II fuzzy controller presents an significant advantage compares to type-I systems because of its better suitability for systems where measures have high levels of uncertainty like those existing in the electric grid or batteries. The controller has been tested on a branch type distribution network, where load demand and energy cost vary dynamically over a three days simulation period.
Keywords: Vehículos eléctricos; Reguladores eléctricos; Sistemas de control inteligente; Automóviles - Baterías; Electric vehicle; Scheduling; G2V; V2G; Fuzzy logic; Type-I; Type-II; Two-stage